Combating and Preventing Corruption in Local Government: Foreign Experience, Administrative, Legal and Criminal Aspects - Shkuta, Oleh; Basko, Andriy; Pozigun, Inna; Pleshko, Eduard; Prodanets, Nataliia (Jurnal Cita Hukum, 2025)
This article is devoted to the negative impact of corruption on the efficiency of the state, the ability of the state to govern, and the deterioration of public life organisations during wartime in Ukraine. The prevention of corruption risks in local government organisations should be carried out by the authorities exclusively at the level of legislative acts. It must comply with the principles of the rule of law and relevant state security. This article presents a detailed analysis of Ukrainian legislation to prevent corruption risks in local self-government organisations (within the administrative and criminal law). It is concluded that strengthening liability for corruption under martial law in Ukraine is fully justified, as it aims to prevent the “reduction” of international aid in wartime, equating corruption with cooperation with the enemy and delivering preventive strikes. A scientific vision of the legislative approach to solving the problem of fighting corruption in Ukraine has been developed, considering the realistic goals of such activities and the war in Ukraine. The following aspects of the legislative approach to the fight against corruption are taken into account: anti-corruption mechanisms at the legislative level and in the activities of executive authorities; formation of an effective system of state bodies that implement the state policy in the field of combating corruption risks; bringing individuals to responsibility for corruption through imprisonment and other measures; intolerance of the population to corruption during the war, etc.  Attention is drawn to the need for states to comply with international standards, namely the recommendations of GRECO and the Istanbul Action Plan of the OECD Anti-Corruption Network.